The Culture of Name-Calling and Shaming by Zimbabwe’s Main Political Parties: A Critical Discourse Analysis - Svongoro, Paul; Mapanzure, Rangarirayi; Madonsela, Stanley (Journal of Cultural Analysis and Social Change, 2026)
Over the past two decades, the Zanu PF party and the Movement for Democratic Change (MDC), led by the late Richard Morgan Tsvangirai, have been characterized by acrimonious relations, leading to rising political tensions and polarization in Zimbabwe. This animosity has been characterised by accusations and counter-accusations of insurgency, banditry, terror and violence by the two protagonists, Zanu-PF on the one hand, and the MDC (and its various formations after the party’s several splits) on the other. While the accusations and counter-accusations by either side have been dismissed as being unwarranted, unproven and unjustified attacks on the other, political analysts have generally described them as being mere political conspiracies and grandstanding by the different political actors. In the context of this background regarding the relationship between Zanu PF and the MDC, this article aims to examine the major accusations and counter-accusations between the two parties, how the accusations have evolved over the past two decades, and how they threatened the security of certain individuals or groups and aided political contests between the two parties. Data for the study were collected from speeches by prominent political figures, newspaper articles, and reports on legal cases in which some of the accusations and counter-accusations were heard in courts of law. The collected data were analysed from the perspective of Fairclough and Wodak’s Critical Discourse Analysis (CDA). From the perspective of CDA, the study analysed how the accusations and counter-accusations made by the two political parties could be regarded as lenses through which we can understand ideological differences and power relations between the two political parties and the socio-political challenges faced by Zimbabwe. The study therefore, contributes to the body of literature on language, politics and security issues in the context of disagreement, conflict of interests and values, uncertainty and power disparities from an African point of view.